The Power of Recognition: Enhancing Employee Performance Through Commitment and Satisfaction - Dwi Andriyanto; Sutianingsih Sutianingsih (Univiversitas Dr. Djar Wattiheluw, 2024)
The study sought to find out how the reward system and job satisfaction of employees can affect their work. It was conducted in The One- Stop-Investment-and- Integrated-Services-Office (DPMPTSP) in Surakarta City, Indonesia. For the sample selection process, individuals used either census or saturated samples. The study used a combination of statistical methods to analyze the data. It is found that various factors, such as organizational commitment and the reward system, have a significant impact on job satisfaction. It's hard to determine exactly how job satisfaction and the reward system affect an employee's performance, but it can help explain why commitment is associated with better performance.